Dinamika Kelembagaan Sumberdaya Lahan dan Konsekuensinya bagi Pembangunan Sektor Pertanian (Forum Penelitian Agro Ekonomi, 2016)
EnglishThe objective of this paper is to provide a comprehensive information on performance development and problems associated with land resource utilisation and its future management perspective. The coverage of discussion to identify such objectives could be divided as follows: (1) perception and concept of land resource, (2) the development of land resource, (3) the importance of land resource, (4) land resource and agricultural production stability, and (5) discussion on policy alternatives to overcome land resource problems. Some important findings could be described as follows: (1) various concepts and ideas on land resource have led to a thought that land resource has social, economic, political values, and a symbol at a certain level as a production factor in agricultural sector, (2) land resource development has changed land resource institutions, land fragmentation, land transfer to other non-agricultural utilization, land value improvement, and polarization and absentee practices, (3) various development activities has reflected the importance of land resource and the highly competitiveness of land utilization in line to the importance of each activity and each sector, (4) acting as a stabilizer in agricultural production, the land resource has faced many problems both in current time or in the future especially those associated with agricultural land degradation reducing land fertileness that ended in marginal land accumulation, in the mean time, food-self sufficiency should be continuously maintained, (5) although all problems on land affairs have been arranged in the UUPA since September 1960; Keppres No. 53/1989 or Keppres No. 33/1990, the problems continually appeared. In this regard, governor, based on Permendagri No. 15/1975, as an officer authorized to issue land utility permit, should launched policies which are very much expected to harmonize the central and local requests, the government and the people, agricultural and nonagricultural sectors, or individual/group requests and the society's needs on land resource. IndonesianTulisan ini bertujuan untuk memberikan informasi tentang perkembangan keragaan dan permasalahan pemanfaatan sumberdaya lahan serta perspektif penanganannya di masa datang. Identifikasi ke arah tersebut dilakukan melalui beberapa subpokok bahasan yang meliputi : (1) persepsi dan konsepsi terhadap sumberdaya lahan, (2) perkembangan sumberdaya lahan berdasarkan waktu, (3) kepentingan terhadap sumberdaya lahan, (4) sumberdaya lahan dan stabilitas produksi pertanian, dan (5) pemikiran terhadap kebijaksanaan dalam mengatasi permasalahan sumberdaya lahan. Beberapa temuan penting yang perlu dikemukakan adalah : (1) beragamnya konsep serta pandangan sumberdaya lahan dalam arti luas memberikan gambaran bahwa sumberdaya lahan mempunyai fungsi sosial ekonomi, politik, serta simbol status tertentu selain sebagai faktor produksi di sektor pertanian, (2) perkembangan sumberdaya lahan berdasarkan waktu telah membawa perubahan terhadap kelembagaan sumberdaya lahan dengan adanya kegiatan fragmentasi lahan, alih fungsi lahan pertanian ke nonpertanian, peningkatan nilai lahan, terjadinya polarisasi ataupun praktek-praktek absentee, (3) adanya berbagai kegiatan pembangunan menjadikan sumber daya lahan sebagai asset yang cukup penting, sehingga terjadi persaingan penggunaan yang cukup meningkat sesuai dengan kepentingan antar aktivitas maupun antar sektoral, (4) sebagai stabilisator bagi produksi pertanian, sumberdaya lahan dihadapkan pada persoalan yang cukup berat baik saat ini dan juga di masa yang akan datang terutama dengan meningkatnya degradasi lahan pertanian, penyusutan lahan produktif yang digantikan dengan lahan marjinal, sementara kebutuhan akan swasembada pangan tetap harus dipertahankan, (5) walaupun secara yuridis permasalahan pertanahan telah diatur dalam UUPA sejak September 1960, Keppres No.53/1989 ataupun Keppres No.33/1990, persoalan mengenai lahan tetap meningkat. Untuk itu kebijaksanaan dari gubernur sebagai pejabat yang berwenang dalam pemberian izin penggunaan lahan sesuai dengan keputusan Permendagri No.15 Tahun 1975 sangat diharapkan sekaligus mampu menselaraskan perbedaan kepentingan antara pusat dengan daerah, penguasa dengan rakyat, sektor pertanian dengan nonpertanian, ataupun kepentingan individu/golongan dengan masyarakat luas terhadap kebutuhan sumberdaya lahan.